Breast Ultrasound. - Stavros, A. Thomas (Wolters Kluwer Health, 2003)
This volume is a complete and definitive guide to performing and interpreting breast ultrasound examinations. The book explains every aspect of the examination in detail-from equipment selection and examining techniques, to correlations between sonographic and mammographic findings, to precise characterization of sonographic abnormalities. A chapter on Doppler characterization of breast lesions is included. Complementing the text are more than 1,500 illustrations, including ultrasound scans, corresponding mammographic images, and diagrams of key aspects of the examination.